2010
DOI: 10.1159/000313360
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome after Double-Balloon Endoscopy in Patients with Obscure Gastrointestinal Bleeding

Abstract: Background and Aims: There are limited data concerning the clinical outcome of patients with obscure gastrointestinal bleeding (OGIB) after double-balloon endoscopy (DBE). The aim of the present study was to evaluate the long-term outcome of patients with OGIB after DBE. Patients and Methods: Eighty-seven consecutive patients with OGIB (47 men and 40 women; mean age 65.3 years) underwent DBE between July 2006 and December 2009. The criteria for assessment included documented iron deficiency anemia/occult or ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
2
17
0
1
Order By: Relevance
“…17 Since then, another 375 studies have been published. These abstracts were reviewed, uncovering another 18 eligible manuscripts [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] reporting on rebleeding rates after endoscopic therapy for angioectasias ( Table 2). Combined with the 6 contained in the AGA technical review, 1 there were a total of 24 eligible endoscopic therapy outcomes papers.…”
Section: Resultsmentioning
confidence: 99%
“…17 Since then, another 375 studies have been published. These abstracts were reviewed, uncovering another 18 eligible manuscripts [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] reporting on rebleeding rates after endoscopic therapy for angioectasias ( Table 2). Combined with the 6 contained in the AGA technical review, 1 there were a total of 24 eligible endoscopic therapy outcomes papers.…”
Section: Resultsmentioning
confidence: 99%
“…If therapeutic DBE is successful, patients in clinically stable condition may be observed depending on the situation. Fujita et al [19] reported that the re-bleeding rate after DBE varied depending on the source of bleeding and patients with treatable lesions had good clinical outcomes after a follow-up period of 41.4 months. In contrast, further treatments such as angiography with interventional radiology or surgery should be considered in patients with evidence of persistent recurrent OGIB.…”
Section: Utility Of Dbe In Ogibmentioning
confidence: 99%
“…However, in Japan, Shinozaki et al [16] and Fujita et al [17] both reported that ulcerative lesions were common. In this paper, the result was 6 cases of vascular lesion, 5 cases of ulcerative lesions, and 1 case of neoplastic lesion.…”
Section: Discussionmentioning
confidence: 99%